The Implementation of Death Penalty in The Context of Islamic Law and Criminal Law in Indonesia: Challenges and Implication - Suwito, Suwito; Adystia Sunggara, Muhammad; Asiyah; Utama, Liza; Beigi, Jamal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
This research aims to answer how the death penalty is regulated in the context of Islamic law and positive criminal law in Indonesia by parsing the challenges and implications. This type of research is conducted with a normative approach, namely by analysing the problem through an approach to legal principles and referring to legal norms contained in legislation. The results show that the death penalty in Islam triggers controversy, where the cons argue that the death penalty does not originate from the Qur'an and Al-Hadith, but is a derivative of the history of the prophet and the Arabs; they are also concerned about human intervention in its implementation so that it is considered not truly from God. On the other hand, the pro side argues that the death penalty is God's will without human intervention. Moreover, in positive criminal law, the death penalty is used to protect the fabric of life and is considered legitimate even though every individual has the right to life. Thus, the state is considered to protect its citizens from unlawful acts.